The relationship between autonomy, supervisor support and work-life balance on employees’ job performance at production and distribution division in Ranhill SAJ Sdn Bhd, Johor Bahru, Johor / Nik Nur Farahini Nik Lah - Nik Lah, Nik Nur Farahini (Faculty of Business and Management, 2020)
Job performance is an individual output in terms of quality and quantity expected from every employee in a particular job. Individual performance is most of the determined by motivation and the will and ability to do the job. The purpose of this study is to identify the relationship between autonomy, supervisor support and work-life balance on employees’ job performance in Ranhill SAJ Sdn Bhd, Johor Bahru, Johor. The study was conducted in Production and Distribution Division in Ranhill SAJ Sdn Bhd, Johor Bahru, Johor. Quantitative method was used and Five Likert-scale questionnaire were distributed to the respondents. The respondents used in this study are 63 people. This study was conducted to determine the relationship between autonomy, supervisor support and work-life balance on employees’ job performance. In addition, the relationship between these factors and their job performance were tested by using Pearson Correlation Coefficient. Multiple linear regression was used to determine the dominant factor that are related with employees’ job performance.